Genetic and epigenetic factors regulating the expression and function of the vitamin D receptor in patients with coronary artery disease - Zh. I. Ionova; E. G. Sergeeva; O. A. Berkovich (Российский кардиологический журнал)
Coronary artery disease (CAD) remains the leading cause of death and disability in developed countries. Using traditional risk factors for CAD, it is possible to predict the likelihood of acute coronary events in no more than 50% of cases. Therefore, the study of influence of genetic and epigenetic factors on the development of CAD is extremely important. Research in recent years has shown that vitamin D deficiency is a new risk factor for atherosclerosis and immune inflammation. Vitamin D implements protective effects against immune inflammation through receptors in the vascular wall. A single nucleotide polymorphism of the vitamin D receptor (VDR) gene is a potential risk factor for CAD associated with low vitamin D levels. VDR expression correlates with the expression of pro-inflammatory cytokines and is regulated by microRNAs — microRNA-125a-5p, microRNA-125b-5p, microRNA-214-3p and microRNA-21 These microRNAs regulate the action, synthesis and metabolism of vitamin D and can themselves be influenced by VDR signals through dynamic feedback, which can lead to destabilization of mRNA and inhibition of translation. This literature review highlights the effect of a single nucleotide polymorphism of the VDR gene and microRNA on the pathogenetic mechanisms of CAD.